State of bare soil surface as a spring drought indicator - MUŽÍKOVÁ, Bronislava; STŘEDA, Tomáš; STŘEDOVÁ, Hana (Contributions to Geophysics and Geodesy, 2013)
To evaluate soil moisture conditions in spring crops sowing term, data of bare soil surface state were used. Analysis included 32 stations throughout the Czech Republic. Number of days with dry soil surface in each year was compared with the average number of those days in the period 1961–2010 for a given station. The limits of the individual categories were then determined for the period 1961–2010. The individual values of the number of days with dry condition of soil in the early spring period were compared with acquired 10th, 25th, 75th and 90th percentile average (1961–2010). More days with dry soil are usually observed in April than in March. In both months there are 11 days with this condition of soil altogether on average. Dry early spring occurred mainly in 1961, 1968, 1974, 1981, 1990, 2002, 2003, 2007 and 2009. Wet spring occurred in years 1965, 1970, 1980, 2001 and 2006 at almost all stations. There is a significant correlation (p < 0.01) between number of days with dry condition of soil and elevation (r = −0.51, n = 32). Average number of days with dry condition of soil surface in March and April in the period 1961–2010 ranges from 5 to 21 days, which is similar to the median values. Trend analysis did not produce conclusive results, but linear trend of smoothing April data was significantly increased in most localities. The number of days with dry condition of soil in the past decades has no significant upward or downward trend. However four years (2002, 2003, 2007 and 2009) have been evaluated as dry and two years (2001 and 2006) were evaluated as wet. An amount of extreme spring weather increases.